1982
DOI: 10.1288/00005537-198207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Postauricular undersurface tympanic membrane grafting: A follow‐up report

Abstract: The authors review 1,939 chronic ear surgeries in which 1,556 underwent some form of tympanic membrane grafting. The overall take rate was 93%. There was no selection of cases with regard to presence of infection, cholesteatoma, polyps, or granulation tissue at the time of surgery. There appeared to be no difference in the take rate based upon age of the patient, presence of infection, or cholesteatoma. Autogenous and homograft fascia performed well and there was no significant difference in take rate. Complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
5

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 16 publications
9
66
0
5
Order By: Relevance
“…The most likely explanation for this is that in most cases of chronic otitis media, even though the ossicular chain may appear normal, there is some factor of scar tissue which prevents total restoration of hearing [9]. The present study's hearing results are comparable to other series [9,10].…”
Section: Hearing Improvementsupporting
confidence: 74%
See 4 more Smart Citations
“…The most likely explanation for this is that in most cases of chronic otitis media, even though the ossicular chain may appear normal, there is some factor of scar tissue which prevents total restoration of hearing [9]. The present study's hearing results are comparable to other series [9,10].…”
Section: Hearing Improvementsupporting
confidence: 74%
“…Paker et al [17] observed one case of debilitating tinnitus post operatively which was associated with sensorineural hearing loss. Glasscock et al [10] reported 1 % incidence of EAC stenosis in his study.…”
Section: Complicationsmentioning
confidence: 76%
See 3 more Smart Citations